Social and solidary economy, work and “gift of self”: Case analysis - Rita Presta, Susana (Cooperativismo & Desarrollo, 2020)
Introduction: From the 90s to the present, successive crises have led to the construction of socio-economic forms of organization anchored in the social and solidary economy. However, these practices of resistance have been colonized by different sectors in relation to the rationality of neoliberal government. Methodology: We focus on our fieldwork (2011-2016) carried out in two artisanal textile value chains, located in Córdoba and Entre Ríos (Argentina). From a relational approach, we analyze multiple dimensions to understand the forms of power construction and subjects. Results: Within the framework of the construction of the social and solidary economy device, the colonization of the affections and the government of the possible have been two technologies of government of subjects articulated with the purpose of managing the social conflict. There is a transfer of the costs of reproduction of the labor force either towards each productive unit or individual. This occurs when the salary-form is dispensed with, at the same time that the work processes and the goods produced remain market-oriented. Conclusions: It is possible to propose “indirect” forms of surplus value, where the “gift of self” and the “waiting time” constitute a central dimension in the forms of subordination of work processes to the market.